RETRACTED: High Glucose Activated Cardiac Fibroblasts by a Disruption of Mitochondria-Associated Membranes - Zhang, Ling-Yu; Lin, Rui-Ting; Chen, Hao-Ran; Yang, Yong-Cong; Lin, Meng-Fei; Tian, Lei-Gang; Pan, Zhi-Qiong; Lin, Lin; Zhu, Liang-Liang; Gu, Zhen-Jie; Chen, Xue-Wen; Li, Yu-Jing; et al. (Frontiers in Physiology, 2021)
Cardiac fibrosis is evident even in the situation without significant cardiomyocyte loss in diabetics cardiomyopathy and high glucose (HG) independently activates cardiac fibroblast (CFs) and promotes cell proliferation. Energy metabolism mainly refer to mitochondrial respiration and glycolysis, which are the key for cell proliferation and the mitochondria-associated membranes (MAMs) are critically involved in regulating MAMs. However, the roles and the underlying mechanism of MAMs in HG-induced CFs proliferation are largely unknown. Proliferation and apoptosis of cardiac fibroblast responding to high glucose treatment were evaluated. MAMs were quantified and mitochondrial respiration and cellular glycolytic levels were determined using Seahorse XF analyzer. Changes of signal transducer and activator of transcription 3 (STAT3) and mitofusin-2 (MFN)2 in responding to HG were also determined and their effects on cell proliferation, MAMs, and mitochondrial respiration were assessed. The effects of STAT3 on MFN2 transcription was determined by dual-luciferase reporter assay (DLRA) and chromatin immunoprecipitation (CHIP). HG induced CFs proliferation and increased glycolytic levels and adenosine triphosphate (ATP) production while mitochondrial respiration were inhibited. MAMs and MFN2 expression were significantly reduced upon HG treatment and the restoration of MFN2 expression counteracted the effects of HG on cell proliferation, MAMs mitochondrial respiration, glycolytic levels, and ATP production. Mitochondrial STAT3 contents were not changed by HG but phosphorylated-STAT3 and nuclear STAT3 were increased. Inhibition of STAT3 reversed the reduction of MFN2 levels induced by HG. DLRA and CHIP directly demonstrated the negative regulation of MFN2 by STAT3 at transcription levels via interacting with sequences in MFN2 promoter region locating at about -400 bp counting from the transcription start site. The present study demonstrated the HG independently induced CFs proliferation via promoting STAT3 translocation to nucleus, which switched mitochondrial respiration to glycolysis to produce ATP by inhibiting MAMs in a MFN2-depression manner.